Executable System Design - Najafzadeh, Amir Morteza; Farahani, Shohreh (My University, 2012)
Software models are important in building large software systems. Even though these models are used to simplify the software system, they can be in themselves, quite complicated. It is not all clear how to build these software models in the best way. This work tackles that problem. We show how one can start with an abstract platform independent model (PIM) and transform it into the complete PIM. The complete PIM is the one which can be translated into a platform specific model (PSM). At each level of the abstraction the PIM is executable and testable. We have done a case study within Ericsson.
Keywords: Datavetenskap (datalogi); Computer Science